Pengaruh Pelatihan Perawatan Kesehatan Masyarakat Terhadap Pemahaman Etik Keperawatan Mahasiswa Ners STIKes Maranatha Kupang - Antonius Rino Vanchapo; Ni Made Merlin; Emmanuel Suban Bala Lewar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background. Nursing profession students are nurses in the future who are expected to work professionally. Professional nurses have a good understanding of nursing ethics, to prevent malpractice when providing nursing services. Efforts to increase konwledge of nursing ethics through community health training. Purpose. The purpose of this study was to determine the effect of the community health training on the knowledge of nursing ethics in nursing profession student of STIKes Maranatha Kupang. Method. Design in this study was a quasy-experiment with one group pre-posttest only. Sample in this study were 50 nursing profession student. The technique sampling was used total sampling method. Process of data collection using a questionnaire related to nursing ethics with 10 questions. Statistical test used Wilcoxon test. Results. Statistical test results obtained p-value